Bacillus coagulans as an alternative to antibiotics in the performance and control of Salmonella Enteritidis in broilers - Lacerda , Dielly Inêz de Oliveira; Maciel, Mônica Patricia; Araújo , Wagner Azis Garcia de; Aiura, Felipe Shindy; Gonçalves , Deyvison da Silva; Brito , Hebert Fernandes de (Revista de Ciências Agroveterinárias, 2022)
The use of antimicrobial growth promoters in broiler feed has been beneficial for improving performance and preventing diseases. However, the indiscriminate use of these products in the feed can result in the development of resistant bacteria, the accumulation of residues in the products, and an imbalance in the microflora of birds. Therefore, it is necessary to evaluate alternatives, such as beneficial microorganisms that improve microbial growth without affecting animal health and product quality. This research aimed to evaluate the supplementation with the probiotic Bacillus coagulans on the performance, carcass characteristics, and health of broilers from seven to 42 days. In total, 720 broilers were used, distributed in a randomized block design with six treatments and eight replicates. The evaluated treatments were as follows: Control ration (RC); PROB1 (Probiotic 400 g/t); PROB2 (Probiotic 400 g/t until 21 days and 200 g/t from 22 to 42 days); RC + antibiotic; RC + Salmonella inoculation; PROB1 + Salmonella inoculation. The treatments did neither influence feed intake, carcass yield, and cuts nor the incidence of injuries to the chest, hock, and footpad. Weight gain and feed conversion were better in birds that received antibiotic or probiotic diets. There was an incidence of Salmonella in the e challenges excreta at 42 days only in the treatment with challenge without adding probiotics. We conclude that the probiotic Bacillus coagulans can be used as an alternative to antibiotics in the diet of broilers as it facilitates similar performance and is efficient in the control of Salmonella Enteritidis.